Prevalence of obesity according to body mass index, waist circumference, and waist-to-height ratio in Peru: A systematic review and meta-analysis - Luisa Erika Milagros Vásquez-Romero; Fiorella E. Zuzunaga-Montoya; Joan A. Loayza-Castro; Enrique Vigil-Ventura; Willy Ramos; Víctor Juan Vera-Ponce (Obesity Pillars)
Introduction: Obesity is a global public health epidemic with significant health implications. However, studies on the prevalence of obesity in Peru have yielded varied results, highlighting the need for updated data to inform effective public health policies. Objective: The primary objective of this study is to determine the prevalence of obesity in Peru using three anthropometric measures: body mass index (BMI), waist circumference (WC), and waist-to-height ratio (WHtR). Methods: Between March and April 2024, a systematic review of published studies reporting the prevalence of obesity in Peru was conducted. The databases Scopus, Web of Science, Embase, PubMed, LILACS, and Scielo were Searched. Results: Overall, the prevalence of obesity was 23.23 %, 38.90 %, and 81.53 % according to BMI, WC, and WHtR, respectively. However, these figures show wide variability, ranging from 13.10 % to 37.4 % according to BMI and from 19.4 % to 51.6 % according to WC. The highest reported prevalence of obesity by WHtR was 85.4 %. Nonetheless, only a fraction of these studies were published in the last five years, and few specifically focused on obesity as the primary objective. Conclusions: The prevalence of obesity in Peru varies significantly depending on the anthropometric measure used. To improve the collection and frequency of data on obesity in Peru, it is recommended that cut-off points be standardized to be suitable for the country and that annual national surveys specifically designed for this purpose be implemented.